Psychological-Pedagogical Training of Professional Education in Ukraine - Tytova, Nataliia; Katsero, Oksana; Yatsenko, Valentina (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2019)
In the article substantiation of theoretical and methodological foundations of professional training of teachers of vocational training in ZVO, the system of their psychological and pedagogical training was developed and experimentally tested.